Implementation of Amercement in the Financing Contract in Islamic Banking based on Justice & Benefits Principles - Imam Rasyidin (Sultan Agung Notary Law Review, 2021)
In Islamic banks, the success or failure of debtors in paying their obligations to Islamic banks has a direct effect on wealth creation for depositors and owners, even for bank employees. The more successful debtors are in paying their obligations and/or providing income to the bank, the higher it will create wealth for depositors and other stake holders. However, the interests of debtors who have a vital role are still not fully accommodated in the agreement set forth in the Islamic bank financing contract. This is because the articles of financing contracts still contain clauses that are burdensome to debtors, namely amercement clause imposed on debtors when they are late in fulfilling their obligations to Islamic banks. The purpose of this study is to describe (1) the application of amercements in financing contracts in Islamic banking (2) the implications of applying amercements in Islamic banking financing contracts to the principles of justice and expediency (3) example of deed of financing in Islamic banking. This study uses sociological juridical methods to find out the exposure or explain legal phenomena as law in action, described as empirical social phenomena at PT. Bank Syariah Indonesia Cirebon Area, whether the implementation of amercements in the financing agreement has there been a match between the applicable regulations and the social reality. The results of this study conclude as follows: Based on the opinion of the majority of scholars', amercements for lateness, negligence and breaking promises are not allowed by syara', when the original obligation is in the form of debts or even payments, because these amercements can be categorized as usury and the law becomes law usury so that it is forbidden by sharia.